APPLICATION OF TAGUCHI EXPERIMENT FOR THE COMPOSITION OPTIMIZATION OF RAW MATERIAL IN MAKING OF TERRAZO CHAIR - Oyong Novareza (Journal of Environmental Engineering and Sustainable Technology, 2017)
Sentra Sanitair Karang Besuki is one of the Small Medium Enterprises that develops in Malang city. One of the products that become observations object in this research is the terrazzo materials seat. One of the problems is the absence of raw material composition standard used for producing terrazzo materials seat. To determine the raw material composition standard, experiment is done using taguchi method. Based on the reference, compression strength should be at least comply with the standard rules by the Indonesian reinforced concrete regulation (pbi 1971 n.i.-2) that is 2nd grade of concrete with k175 standard. There are four factors that considered has impact on the compression strength of terazzo material seat, that is cement, crushed rocks, grit, and mill. The orthogonal array design used in this experiment is L9 (34). The optimal setting obtained from this experiments is 3rd level for A factor (cement: 30%), 2nd level for B factor (Crushed rocks: 22.5 %), 1st level for C factor (grit: 37.5%), and 3rd level for D factor (mill: 10%). The confident interval obtained in this taguchi experiment is 177.24+2.61 for the average value and 32.41+3.71 for the variance (SNR). While the confidence interval in the confirmatory experiments is 165.9+15.65 for the average value and 34.48+4.03 for the variance (SNR). So it is concluded that the optimal setting level of the terrazzo materials seats is acceptable because the confident interval of the confirmatory experiment is still in the optimal interval results.